Chitooligosaccharides suppress airway inflammation, fibrosis, and mucus hypersecretion in a house dust mite-induced allergy model - Yun-Ho Kim; Chan-Ho Park; Ju Myung Kim; Yeo Cho Yoon (Frontiers in Allergy)
BackgroundRespiratory allergy is a serious respiratory disorder characterized by inflammation, mucus hypersecretion, and airway tissue sclerosis. Disruption of the T helper 1 (Th1) and T helper 2 (Th2) immune systems by stimuli induced by house dust mites (HDM) and fine particulate matter leads to the secretion of various inflammatory cytokines, resulting in immune respiratory diseases characterized by airway inflammation. Chitooligosaccharides (COS) are known for their antioxidant and anti-inflammatory properties.MethodsHuman airway epithelial cells (BEAS-2B) were cultured in DMEM/F12 medium containing COS at concentrations of 25–100 µg/ml for 24 h. No intracellular toxicity was observed up to 1,000 µg/ml. Cell experiments were conducted at COS concentrations below 100 µg/ml, while animal experiments were performed at concentrations below 100 mg/kg body weight for 4 weeks. Samples of right lung tissue obtained from the experimental animals were used for gene and protein expression analysis, whereas samples of contralateral lung tissue were used for immunohistochemical analysis.ResultsCOS regulated Th1 immunity by inhibiting major cytokines, including inflammatory tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6), in BEAS-2B cells. In the HDM-induced allergic respiratory model, COS suppressed the infiltration of inflammatory cells around the airways and inhibited the mRNA expression of Th1 immune cytokines in lung tissues, while also reducing the expression of nuclear factor kappa B (NF-κB)-related proteins. Furthermore, the results confirmed the suppression of the levels of immunoglobulin E (IgE) in the blood secreted by mast cells activated by HDM, which led to a reduction in allergic mucus hypersecretion and airway sclerosis.ConclusionIn summary, COS are thought to improve airway resistance by alleviating inflammatory allergic respiratory diseases caused by HDM and are regarded as substances that regulate the balance of the Th1 and Th2 immune systems in epithelial cells affected by mucus hypersecretion.